IMPLEMENTASI QR CODE VALIDATION PADA SISTEM INFORMASI SURAT PERINTAH PERJALANAN DINAS - Adri, Ara Fa; Suni, Alfa Faridh (Jurnal Sistem Komputer, 2020)
Abstract— Quick Response Code (QR Code) is a two-dimensional barcode that is able to provide more information than a one-dimensional barcode. Smart phone technology that develops very fast with advanced camera facilities equipped with scanning and decoding qr code features. The camera reads the QR code in five parts, namely pattern, alignment, timing pattern, quiet zone, and data area. The five sections used the qr code library to translate back in numbers or letters quickly. Compared to one-dimensional barcodes, qr code is more useful because it can store numbers or letters, while one-dimensional barcodes can only store numbers. The advantage of the QR code that can store numbers and letters is the choice of the company in using the QR code as a support system for official travel orders made in a website-based program.